KARAKTERISASI SIMPLISIA SKRINING FITOKIMIA DAN UJI TOKSISITAS EKSTRAK ETANOL HERBA BINTARO (Cerbera manghas L.) TERHADAP Artemia salina Leach - Nasution, Haris Munandar; Fatimah, Cut; Syara, Nurdiani (Jurnal Farmanesia, 2019)
The use of anticancer chemotherapy with chemicals has not given optimal results because the drug does not work specifically, in addition to attacking cancer cells it also damages normal cells. Bintaro (Cerbera mangha L.) is a wild plant that contains secondary metabolites which have been shown to have a wide range of therapeutic applications. Several studies have stated that Bintaro has activities as aanti cancer. The purpose of this researchto know the characteristics of Bintaro herb simplicia (Cerbera manghas L.) which can be determined using the procedures listed in the Materia Medika Indonesia book, knowing the class of secondary metabolites contained in the ethanol extract of bintaro herbs (Cerbera manghas L.), andknowing the level of toxicity of the ethanol extract of the herb bintaro (Cerbera manghas L.). The method used in this research is experimental with the post-test only controlled group design. The results of the characterization on the organoleptic test of Bintaro herb simplicia, namely the leaves are dark brown, the taste is slightly bitter then bitter, the stems are dark brown and shrinking, the smell is distinctive and tasteless, and the flowers are dark brown, characteristic odor and tasteless, after being ground to a powder. dark brown. The results of the microscopic test, the leaf herb simplicia samples obtained fragments, namely diasitic type stomata, spiral vessel fragments and upper epidermis fragments with palisade cells. As for the stem herbs, there were tissue fragments of sclerenchyma fibers, vessel fragments, parenchymal fragments with clumps of brown secretions. Sclereid fragments were found in the floral herb samples.6%, for determination of water-soluble extract content obtained = 20.06%, ethanol soluble extract content = 2.18%, total ash content = 12.62%, acid insoluble ash content = 6.11%. positive bintaro herbs contain compounds of alkaloids, flavonoids, steroids, tannins and saponins. From the calculation of the LC50 value, it can be concluded that the entanol extract of the Bintaro herb is included in the very toxic category with a value ofLC50 < 30 g/mlthat is9.35g/mL.